A new species of the genus Serrundabracon van Achterberg (Hymenoptera: Braconidae: Braconinae) from Namibia - Quicke, Donald L. J.; Butcher, Buntika A. (Zootaxa, 2015)
A second species of the braconine genus Serrundabracon is described and illustrated and distinguished from the type species, S. maraisi Braet. Both species possess the unique combination of a multiple-arched ovipositor and dentate posterior margin to the metasomal tergite 5. Corrections are made to the redescription of S. maraisi. The relationships of, and possible evolutionary transitions to, the genus are discussed.